The Impact of IT Expenses and Assets on Administrative Costs in Local Governments - Ishikawa, Keiko; Sato, Toru; Kuroki, Makoto; Yamamoto, Kiyoshi (Accounting Progress, 2024)
This study investigates the impact of IT expenses and assets on administrative costs in local governments. IT costs incurred by local governments can contribute to the reduction of future administrative costs by improving service processes through online administrative procedures, increasing business efficiency through data utilization and digital transformation, and introducing cloud computing in local governments. Further, based on the uniformed accounting standards in Japanese local governments, “software” could be measured if it reduces future costs through the use of such software. We hypothesize that there is a negative relationship between IT expenses/software and administrative costs in local governments. The empirical results show that the coefficient of the IT expenses is not statistically significant, while the coefficient of the software is consistently estimated to be positive and significant in relation to current and future administrative costs. These results suggest the low possibility that IT expenses and assets in local governments improve administrative costs, rather IT expenses and assets may be temporarily worsen their administrative costs.